EFEKTIVITAS MOLUSKISIDA BUAH PINANG BERBENTUK PADAT DAN CAIR TERHADAP TINGKAT KEMATIAN KEONG MAS (Pomacea canaliculata) PADA TANAMAN PADI - Abdul Rahim; Desy Resky Oktavia; Nurmaisah Nurmaisah (Jurnal Agrotek Ummat, 2021)
Molluscicide made from areca nut is an alternative pesticide to control snail pests. Comparing the effects of solid (powder) and extract (liquid) types of molluscicide is an effort to develop these pesticides. This study was aimed to compare the effect of using molluscicide with active ingredients of fentin acetate, areca nut powder, and extracts on golden snails in rice plants. The study used a randomized block design (RCBD), with two factors. The first factor was the type of molluscicide, namely fentin acetate, powder, and areca nut extract. Meanwhile, the second factor was the dose consisting of the recommended dose and half the recommended dose. There were 6 treatment combinations that were 5 replications. The research data consisted of mortality rates, 1, 2, 3, 7, and 14 days after applications. Data were analyzed used non-parametric analysis of variances by Kruskal-Wallis and Man Whitney Test. The results showed that there were effects of fentin acetate, areca nut powder, and extract on the mortality rate of the golden snails. The mortality rate reached 50%-75% at 3 days applications and reached 98%-100% at 7 days after applications. Furthermore, there was also showed that areca nut powder molluscicide could be an alternative to synthetics molluscicide because the areca powder nut powder tended to be more effective than other pesticides with half the recommended dose.